2020
DOI: 10.2147/ijn.s227931
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Chelate-Free Nano-Platform for Incorporation of Diagnostic and Therapeutic Isotopes</p>

Abstract: Purpose: Using our chelate-free, heat-induced radiolabeling (HIR) method, we show that a wide range of metals, including those with radioactive isotopologues used for diagnostic imaging and radionuclide therapy, bind to the Feraheme (FH) nanoparticle (NP), a drug approved for the treatment of iron anemia. Material and methods: FH NPs were heated (120°C) with nonradioactive metals, the resulting metal-FH NPs were characterized by inductively coupled plasma mass spectrometry (ICP-MS), dynamic light scattering (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Heat-Induced Radiolabeling (HIR) HIR was carried out according to the published protocol. 7,10 Briefly, three identical FH samples were prepared, two for radiochemical analysis and one for phantom imaging. For each sample, the reaction mixture was prepared by adding 20 µL [ 89 Zr]Zr (m Zr ≈ 0.0125 nmol, N atoms ≈ 7.5×10 12 , with A 0 ≈18.5 MBq) and 50 µL CTW into a 0.3 mL glass vial.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Heat-Induced Radiolabeling (HIR) HIR was carried out according to the published protocol. 7,10 Briefly, three identical FH samples were prepared, two for radiochemical analysis and one for phantom imaging. For each sample, the reaction mixture was prepared by adding 20 µL [ 89 Zr]Zr (m Zr ≈ 0.0125 nmol, N atoms ≈ 7.5×10 12 , with A 0 ≈18.5 MBq) and 50 µL CTW into a 0.3 mL glass vial.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…This is also consistent with our previous study. 7 The inductively coupled plasma mass spectrometry analysis of a range of HIR labeled metal-FH products demonstrated that all of Sr 2+ , Ba 2+ , Mo 3+ , Pb 2+ , Cu 2+ , Bi 3+ , In 3+ , Y 3+ , Lu 3+ , Sm 3+ , Tb 3+ , and Eu 3+ cations were adsorb onto the FH surface via Radiocation Surface Adsorption. 7 The labeling yield (LY) is calculated using Equation (1), with the change in volume per FH particle,…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
See 3 more Smart Citations